The multi-functional foot in athletic movement: Extraordinary feats by our extraordinary feet - Wilson, J.; Kiely, J. (Human Movement, 2016)
The unique architecture of the foot system provides a sensitive, multi-tensional method of communicating with the surrounding environment. Within the premise of the paper, we discuss three themes: complexity, degeneracy and bio-tensegrity. Complex structures within the foot allow the human movement system to negotiate strategies for dynamic movement during athletic endeavours. We discuss such complex structures with particular attention to properties of a bio-tensegrity system. Degeneracy within the foot structure offers a distinctive solution to the problems posed by differing terrains and uneven surfaces allowing lower extremity structures to overcome perturbation as and when it occurs. This extraordinary structure offers a significant contribution to bipedalism through presenting a robust base of support and as such, should be given more consideration when designing athletic development programmes.